Pattern formation in a horizontally shaken granular submonolayer - Krengel, Dominik; Strobl, Severin; Sack, Achim; Heckel, Michael; Pöschel, Thorsten (Granular Matter, 2013)
We study the mechanism leading to the formation of stripe-like patterns in a rectangular container filled with a sub-monolayer of frictional spherical particles when it is subjected to horizontal oscillations. By means of Molecular Dynamics simulations we could reproduce the experimental results. Systematic simulations allow to identify friction to be responsible for the pattern formation, that is, the tangential interaction between contacting particles and between the particles and the floor of the container. When particles are in contact with the floor and other adjacent particles simultaneously, there emerges a frustrated situation in which the particles are prevented from rolling on the floor. This effect leads to local jamming and eventually to stripe-like pattern formation. In the long time evolution, the stripes are unstable. Stripes may merge as well as disintegrate. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Frustration effects; Horizontal shaking; Pattern formation